Improving Community Economic Resilience through Biogas as a Sustainable Alternative Energy - Khairunnisa, Dhiya Atha; Andriyani, Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: The study aims to assess the potential of biogas derived from cow manure to replace LPG in rural households, while strengthening community resilience and improving economic conditions.Methodology: A descriptive quantitative approach was applied, using statistical analysis of data collected from 39 households in Mundu Village, Tulung District, Klaten Regency that actively use biogas.Results: The findings show that biogas usage leads to a 75% reduction in LPG consumption and generates monthly savings ranging from IDR250,000 to IDR300,000. The average initial investment of IDR8.6 million indicates strong long-term economic feasibility.Applications/Originality/Value: This research offers empirical evidence on the viability of biogas as an alternative household energy source in rural Indonesia, highlighting its capacity to decrease dependence on fossil fuels through locally available resources.